PERANCANGAN APLIKASI PENGOLAHAN DATA ADMINISTRASI PADA SEKOLAH DASAR NEGERI 16 KAYU AGUNG - Muhammad Sobri; Suyanto Suyanto (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
This study aims to assist and facilitate the administration of particular data processing student data, teacher data, facilitate the search for student data and teacher data, and make the data - the data is computerized and systematically arranged. This research method using waterfall method stages - stage consists of system requirements analysis, system design, writing code, testing programs and maintenance of applications, while the data collection method using the library research such as collecting data through a book - a book or magazine that is relevant to relate to application to be built. With this application, it is expected that schools have become schools for which data are computerized, so that it can improve the quality of administrative services at the school.